Inframammarial Giant Fibroadenoma Removing and a Nipple-sparing Breast Reconstruction in an Adolescent: A Case Report - Ilhan Ciftci; Tamer Sekmenli; Seda Ozbek; Mehtap Karamese; Serdar Ugras (Prague Medical Report, 2015)
Fibroadenomas are common, benign breast tumors that usually affect women in the second and third decade of life. Giant fibroadenomas often cause significant concern for the patient or family regarding malignant potential and altered breast development. Most fibroadenomas are benign. Local excision of small lesions through a circumareolar or inframammary incision rather than radical surgery is appropriate. Breast ultrasound represents the most commonly used imaging modality for the study of pediatric female breast masses and fibroadenomas. Detailed descriptions of the sonographic appearances of fibroadenomas in young girls are sparse. We believe that surgical treatment for the patient should include tumor extirpation and immediate restoration of breast appearance, minimizing visible scars, protection of the developing breast bud, nipple, and areola. This modality reduces psychosocial comorbidity.